Erratum to “The Difference between Coagulation Profile and Fibrinolysis in Acute and Chronic Leukemia Patients”[Published Issue of Indonesian Journal of Clinical Pathology and Medical Laboratory March 2025, 31(2) : p. 136] - Limijadi, Edward Kurnia Setiawan; Devi, Wivina Riza; Tjitradinata, Cynthia (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
This erratum is to explain a typographical error in Table 2 occurred in the published issue of Indonesian Journal of Clinical Pathology and Medical Laboratory Volume 31, Number 2 in March 2025, pages 136. The error was in writing the Fibrinogen level which should be a period, not a comma and D-dimer level in the table, which should be a comma, not a period.